Samsung Lithium Ion Battery for Uninterruptible Power Supply - Sithole, Tshepo; Veerdhi, Vasudeva Rao; Sithebe, Thembelani (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2025)
Samsung's energy storage systems for data centres are pioneering, being the first lithium-ion battery cabinets to meet stringent UL rack-level safety standards. Integrating an Uninterruptible Power Supply (UPS) with an energy storage system is essential for ensuring reliable power to critical loads. Samsung lithium-ion battery systems are engineered to exceed the demands of large-scale UPS applications. This paper reviews, implements, and analyses Samsung lithium-ion batteries compared to lead-acid batteries, particularly with the Vertiv UPS system. A 400 kVA Vertiv UPS was connected to 17 Samsung SDI lithium-ion batteries in a robust rack configuration, each rated at 30.4 Vdc and 67 Ah. Simultaneously, a lead-acid battery setup consisting of forty 12V 67Ah batteries housed in a specialized cabinet was evaluated. A 360 kW resistive load was applied to the UPS output, and an external mains failure was simulated while measuring end-of-discharge time. Results showed that the Samsung SDI lithium-ion battery system reached a cut-off voltage of 393.5 VDC at 954.0 A, achieving 58 minutes of runtime, while the lead-acid system recorded 395.2 VDC at 962.0 A, lasting 49 minutes. These findings confirm the superior performance of lithium-ion batteries in UPS applications, reinforcing their role in data centre energy storage.